FRAMING OF THE CERTIFICATION Of ROUNDATABLE ON SUSTAINABLE PALM OIL (RSOP) FARMER'S ASSISTANCE PROGRAM STRATEGY IN SOUTH TAPANULI WITH ASSET-BASED COMMUNITY DEVELOPMENT APPROACH (Study Case of Unilever Assisted Farmer Groups) - Fikri Latief Adrian; Meilita Tryana Sembiring; Chairul Muluk (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2023)
The agricultural sector is one of the crucial sectors in Indonesia, which is the primary source of food and economic growth. The role of this sector can still be increased if appropriately managed. In today's international trade, sustainability is one of the most important things to maintain, embodied in the Roundtable on Sustainable Palm Oil (RSPO) certification. Corporate Social Responsibility (CSR) policies can be used as one of the strategies carried out by companies in community empowerment. The Asset-Based Community Development approach can create an effective and sustainable program. This is done with the stages of discovery, dream, design, define, and compare. As a result, all assets owned are mapped for human, financial, social, physical, and natural assets. The targets expected by the farmer group community are to build the commitment and independence of farmer groups in program sustainability, increase the income of independent smallholders who have obtained RSPO certificates, and increase the number of independent smallholders certified each year. The strategy is prepared based on the derivatives of the expected targets for each farmer group actor, Unilever, academics, and local government.